IMF-Supported Programs and Crisis Prevention : An Analytical Framework - Kim, Jun (IMF Working Papers; Working Paper, 2006)
This paper presents an analytical framework for considering the role of IMF-supported programs in preventing crises, particularly capital account crises. The model builds upon the global games framework to establish a unique relationship between the crisis probability and the parameters of the program, which is assumed to be negotiated between the IMF and the member country, taking explicit account of each party's interests. In the model, from the perspective of the borrowing country, IMF financing and policy adjustment are (perfect) substitutes inasmuch as they both contribute to the country's liquidity and thus reduce the likelihood of a crisis. In equilibrium, however, IMF financing promotes stronger policies, implying that financing and adjustment are strong complements in crisis prevention. Conditionality plays a crucial role in sustaining the program, providing mutual assurances-to the member country that, if it undertakes the agreed policies, financing will indeed be forthcoming, and to the IMF that the country will implement the agreed policies as the IMF disburses its resources. The model helps explain how liquidity crises may come about, how IMF support can reduce the likelihood of a crisis by providing liquidity and sustaining stronger policies, and why the observed mix between financing and adjustment may vary across programs.